Hallumi Type Cheese Production Technology and Its Nutritive Value - Kapshakbayeva, Zarina; Mayorov, Aleksandr; Moldabayeva, Zhanar; Baitukenova, Sholpan; Utegenova, Asiya; Okuskhanova, Eleonora (International Journal of Engineering and Technology, 2018)
Nowadays in Kazakhstan the assortment of products produced from goat's milk is currently not so great. The main problem with the lack of products based on goat's milk is that goat's milk, as an industrial raw material, has been little studied. This article examines the effectiveness of the use of goat milk in the production of cheese type halloumi. According to the studies, it was found that the use of whole milk for cheese production allows increasing the yield of the finished product. Also an enzyme preparation is selected, which ensures the optimal process ofÂ goat's milk proteins coagulation. The article also reflects the results of a comparative analysis of an experimentally produced cheese sample with authentic Halloumi cheese made in Cyprus.Â Â